Pentingnya Evaluasi Pembelajaran pada Tingkat Sekolah Dasar di SD Negeri 194/VI Tambang Emas I - Sastrawati, Eka; Indryani, Indryani; Nazurti, Nazurti; Darwin, Carles; Syifa, Putri (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to determine students' abilities regarding evaluations carried out by teachers at SD Negeri 194/VI Tambang Emas I. This research is a type of Classroom Action Research. Implementing classroom learning will have an impact on increasing teacher abilities, because a competent teacher is a teacher who is able to manage the class and evaluate students individually and in groups. Learning evaluation is a process of determining the level of achievement of predetermined learning objectives through a systematic method. Learning evaluation aims to collect information that is the basis for measuring the level of progress, development and learning achievements of students, as well as the effectiveness of educators in teaching. The results of the research show that teachers at SD Negeri 194/VI Tambang Emas I will provide an evaluation after repeating the lessons that have been learned and after that the teachers explain the lessons that will be learned using observation media for students so that students find out for themselves and after that the teacher will explain.